Flexible Retrieval Mechanisms Supporting Successful Inference Produce False Memories in Younger but not Older Adults - Carpenter, Alexis C. (Psychol Aging, 2018)
Episodic memory involves flexible retrieval processes that allow us to link elements of distinct episodes in order to make novel inferences across events. In younger adults, we recently found that the same retrieval-related recombination mechanism that supports successful associative inference produces source misattributions as a consequence of erroneous binding of contextual elements from distinct episodes. In the current experiment, we found that older adults, in contrast to younger adults, did not show an increase in source misattributions following successful associative inference. We observed this pattern both when (A) younger and older adults were tested under identical experimental conditions, and (B) younger and older adults were matched on associative inference accuracy and overall source memory errors. We suggest that the differing patterns of results are a consequence of age-related deficits in associative binding during successful inferential retrieval.